2021
DOI: 10.1177/15394492211012654
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Household Income and Functional Independent Behavior for Children With Autism

Abstract: Children in lower income households are less likely to be diagnosed with autism spectrum disorder (ASD) and diagnosis is often delayed. Lack of or delayed identification of ASD minimizes a child’s ability to receive effective early intervention services that support development of functional independence skills. Research has yet to identify relationships between functional independence and household income for children with ASD. A cross-sectional national survey with 231 caregivers of children with autism aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
(53 reference statements)
1
3
0
Order By: Relevance
“…Our results also replicate recent work demonstrating race related differences in Vineland Communication scores (Fombonne & Zuckerman, 2022) but not in other aspects of social functioning. Finally, similar to recent reports (St. John & Ausderau, 2021), we found that families with lower household income reported lower social communication skills across some scales of the Vineland, SRS, and PDDBI, whereas ADI, Vineland, AIM, and PDBBI scores differed by parental education. Given these patterns of non-equivalence, including some replicated elsewhere, it is important to recognize that characterization of ASD social behaviors may be influenced by the sample composition with respect to child and family factors.…”
Section: Discussionsupporting
confidence: 93%
“…Our results also replicate recent work demonstrating race related differences in Vineland Communication scores (Fombonne & Zuckerman, 2022) but not in other aspects of social functioning. Finally, similar to recent reports (St. John & Ausderau, 2021), we found that families with lower household income reported lower social communication skills across some scales of the Vineland, SRS, and PDDBI, whereas ADI, Vineland, AIM, and PDBBI scores differed by parental education. Given these patterns of non-equivalence, including some replicated elsewhere, it is important to recognize that characterization of ASD social behaviors may be influenced by the sample composition with respect to child and family factors.…”
Section: Discussionsupporting
confidence: 93%
“…A noted rise in positive behavior of children from a middle economic level resulted in the loss of this significant difference. In this context, John and Ausderau [ 26 ] noted that children from higher economic levels had increased functional independence behavior compared with those from lower levels. This perhaps explains the noted association.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has documented links between family demographics (e.g., household income, parent education, ethnic background, and immigrant status) and early identification and diagnosis of autism (Daniels & Mandell, 2014;Thomas et al, 2012), access to and utilization of services (Khanlou et al, 2017;Lim et al, 2021;Pickard & Ingersoll, 2016;Smith et al, 2020), as well as educational placement (Gindi, 2020;Kurth et al, 2016). outcomes (Aishworiya et al, 2021;Hodge et al, 2021;St. John & Ausderau, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has documented links between family demographics (e.g., household income, parent education, ethnic background, and immigrant status) and early identification and diagnosis of autism (Daniels & Mandell, 2014 ; Thomas et al., 2012 ), access to and utilization of services (Khanlou et al., 2017 ; Lim et al., 2021 ; Pickard & Ingersoll, 2016 ; Smith et al., 2020 ), as well as educational placement (Gindi, 2020 ; Kurth et al., 2016 ). These factors may further influence Autistic children's adaptive outcomes (Aishworiya et al., 2021 ; Hodge et al., 2021 ; St. John & Ausderau, 2021 ). It is considered important to account for multiple demographic indicators when studying behavioral manifestation of autism to mitigate their confounding effects on the primary factors of interest (Durkin et al., 2017 ; Rai et al., 2012 ).…”
Section: Introductionmentioning
confidence: 99%